Trajectory-Based Classification of Recovery in Sensorimotor Complete Traumatic Cervical Spinal Cord Injury. (1st June 2021) - Jaja, Blessing N.R.; Badhiwala, Jetan; Guest, James; Harrop, James; Shaffrey, Chris; Boakye, Max; Kurpad, Shekar; Grossman, Robert; Toups, Elizabeth; Geisler, Fred; Kwon, Brian; Aarabi, Bizhan; et al.
Abstract : Objective: To test the hypothesis that sensorimotor complete traumatic cervical spinal cord injury (SCI) is a heterogenous clinical entity comprising several subpopulations that follow fundamentally different trajectories of neurologic recovery. Methods: We analyzed demographic and injury data from 655 patients who were pooled from 4 prospective longitudinal multicenter studies. Group-based trajectory modeling was applied to model neurologic recovery trajectories over the initial 12 months postinjury and to identify predictors of recovery trajectories. Neurologic outcomes included upper extremity motor score, total motor scores, and American Spinal Injury Association Impairment Scale (AIS) grade improvement. Results: The analysis identified 3 distinct trajectories of neurologic recovery. These clinical courses included (1) marginal recovery trajectory, characterized by minimal or no improvement in motor strength or change in AIS grade status (remained grade A); (2) moderate recovery trajectory, characterized by low baseline motor scores that improved approximately 13 points or AIS conversion of 1 grade point; (3) good recovery trajectory, characterized by baseline motor scores in the upper quartile that improved to near maximum values within 3 months of injury. Patients following the moderate or good recovery trajectories were younger, had more caudally located injuries, had a higher degree of preserved motor and sensory function at baseline examination, and exhibited a greater extent of motor and sensory function in the zone of partial preservation. Conclusion: Cervical complete SCI can be classified into one of 3 distinct subpopulations with fundamentally different trajectories of neurologic recovery. This study defines unique clinical phenotypes based on potential for recovery, rather than baseline severity of injury alone. This approach may prove beneficial in clinical prognostication and in the design and interpretation of clinical trials in SCI.